Mendelian Randomized Study of Protective Effect of Statins on Breast Cancer - Hu, Di; Shui, Yifang; Miao, Keke; Li, Mengquan (Zhongliu fangzhi yanjiu, 2025)
Objective　To genetically investigate the protective effects of statins on breast cancer. Methods　Instrumental variables for the statin target gene HMGCR and five other cholesterol-regulated genes (LDLR, PCSK9, ABCG8, APOB, and NPC1L1) were obtained from previous expression quantitative trait locus (eQTL) studies. Cholesterol-regulated genes predicted by these instrumental variables served as the exposure factors. Mendelian randomization based on pooled data (SMR) was conducted to explore the genetic effects of exposure factors on the incidence risk of all breast cancers, ER+ breast cancer, and ER-breast cancer. Instrumental variables for total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and non-highdensity lipoprotein cholesterol (non-HDL-C) were derived from a previous human genome-wide association study and restricted to be chromosomally located within 100 kb of the above cholesterol regulatory genes; the instrumental variables could predict TC, LDL-C, or non-HDL-C levels under the regulation of the abovementioned cholesterol-associated genes which were used as exposure factors. Two-sample Mendelian randomization (IVW, MR-PRESSO, and MR-Egger) was used to explore the genetic effects of exposure factors on the risk of all breast cancers, ER+ breast cancer, and ER− breast cancer. Results　SMR analysis reported that elevated HMGCR expression was significantly associated with the increased incidence risk of all breast cancers and ER+ breast cancer (P=0.044 and P=0.039, respectively) but not with the change in incidence risk of ER− breast cancer (P=0.190); the other five regulatory genes were not significantly correlated with the change in incidence risk of all breast cancers, ER+ breast cancer, and ER− breast cancer (all P>0.05). IVW analysis reported that under the regulation of HMGCR, elevated levels of peripheral TC, LDL-C, and non-HDL-C significantly increased the incidence risk of all breast cancers (P=1.160e-05, P=1.248e-05, and P=1.869e-05) and the incidence risk of ER+ breast cancer (P=3.181e-04, P=2.231e-04, and P=3.520e-04), but they were not associated with a change in the incidence risk of ER− breast cancer (P=0.062, P=0.133, and P=0.055). The results of MR-PRESSO and MR-Egger analyses supported the IVW results. Conclusion　Statins could reduce the incidence risk of ER+ breast cancer at the genetic level, but there is no such protective effects on ER− breast cancer.